The Effect of lead exposure of mice during pregnancy on the morphology of epididymal and testicular spermatozoa of their offspring - IM, Al-Ani; IN, Al-Khfaji; MB, Fakhrildin; HH, Mangalo; SR, Al-Obaidi (IIUM Medical Journal Malaysia, 2009)
Introduction: The aims of this study were to assess the differences in the percentages of abnormal morphology between the epididymal and testicular spermatozoa of mature male offspring mice whose mothers were injected with various doses of lead acetate during gestation. Materials and Methods: Seventy two healthy female mice were divided into three major groups according to the number of injections involving 1, 2 or 3 injections at 8th day; 8th and 13th days; and 8th, 13th and 18th days of gestation period, respectively. Each major group was subdivided into four minor groups according to the dosage of lead administered (0, 25, 50 and 100) mg/Kg. Results: The percentages of abnormal morphology of epididymal and testicular spermatozoa were studied and the data were statistically analyzed. The results of this study proved that an increased number of injections and/or dose of lead acetate injected to the mothers during gestation cause an elevation in the percentage of abnormal morphology of both epididymal and testicular spermatozoa of the male mice offspring. Conclusion: In conclusion this study demonstrated that lead acetate when exposed prenatally have toxic effects on the sperm in the offspring male mice resulting in abnormal morphology of spermatozoa. The most likely causative factor is disturbances in the phase(s) of spermatogenesis and/or spermiogenesis.